Soa governance optimizes the business and evolution of service oriented systems (2009)
Contiene -- Need for SOA governance -- SOA vs. IT governance -- Characterizing SOA governance -- SOA governance pillars -- SOA governance mechanisms facilitate the optimization of business and evolution objectives of service-oriented systems -- Traditional evolution mechanisms -- Feedback loops -- Levels of indirection -- Research challenges